Exploring the application of metal-based photothermal agents in photothermal therapy combined with immune checkpoint therapy - Xie, Bin; Xiao, ZhiRong; Ling, JiaBao; Peng, Yichao; Chen, Tianfeng (Frontiers in Pharmacology, 2025)
Photothermal therapy (PTT), a popular local treatment that uses heat to ablate tumors, has limited efficacy in addressing metastatic and deeply located tumors when used alone. Integrating PTT with immunotherapy not only yields a synergistic effect but also promotes cancer regression and confers the benefit of immune memory, which can surmount the challenges faced by PTT when used in isolation. Metal-based nanomaterials, renowned for their superior photothermal conversion efficiency and distinctive photochemical properties, have been extensively researched and applied in the field of PTT. This review summarizes the latest developments in combination therapies, with a specific focus on the combination of PTT and immune checkpoint therapy (ICT) for cancer treatment, including a comprehensive overview of the recent advancements in noble metal-based and 2D transition metal chalcogenides (TMDCs)-based photothermal agents, and their anticancer effect when combining PTT with immune checkpoint blockades (anti-CTLA-4 and anti-PD-L1) therapy. The goal of this review is to present an overview of the application, current challenges and future prospects of metal-based photothermal agents in PTT combined with ICT for cancer treatment.